Facile Cell-Friendly Hollow-Core Fiber Diffusion-Limited Photofabrication - Savelyev, Alexander G.; Sochilina, Anastasia V.; Akasov, Roman A.; Mironov, Anton V.; Kapitannikova, Alina Yu.; Borodina, Tatiana N.; Sholina, Natalya V.; Khaydukov, Kirill V.; Zvyagin, Andrei V.; Generalova, Alla N.; Khaydukov, Evgeny V. (Frontiers in Bioengineering and Biotechnology, 2021)
Bioprinting emerges as a powerful flexible approach for tissue engineering with prospective capability to produce tissue on demand, including biomimetic hollow-core fiber structures. Inspite of significancy for tissue engineering, holow-core structures proved difficult to fabricate, with the existing methods limited to multistage, time-consuming, and cumbersome procedures. Here, we report a versatile cell-friendly photopolymerization approach that enables single-step prototyping of hollow-core as well as solid-core hydrogel fibers initially loaded with living cells. This approach was implemented by extruding cell-laden hyaluronic acid glycidyl methacrylate hydrogel directly into aqueous solution containing free radicals generated by continuous blue light photoexcitation of the flavin mononucleotide/triethanolamine photoinitiator solute. Diffusion of free radicals from the solution to the extruded structure initiated cross-linking of the hydrogel, progressing from the structure surface inwards. Thus, the cross-linked wall is formed and its thickness is limited by penetration of free radical in hydrogel volume. After developing in water the hollow-core fiber is formed with centimeter range of length. Amazingly, HaCaT cells embedded in the hydrogel succesfully go through the fabrication procedure. The broad size ranges has been demonstrated: from solid core to 6% wall thickness of the outer diameter, which was variable from sub-millimeter to 6 mm; and Young’s modulus  1.6±0.4 MPa. This new proof-of-concept fibers biofabrication approach opens lucrative opportunities for facile three-dimensional fabrication of hollow-core biostructeres with controllable geometry.